Pemikiran akidah imam al-syafi`i - Nizara, Tamar Jaya (Penerbit UTM Press, 2013)
Imam al-Shafi'i is a big name as a prominent of the Islamic thought. The writings about his thoughts related to the field of Islamic belief are highlighted in this article looking at the position of the Shafi'i’s sect as a main sect for Muslims in Malaysia. By highlighting the discussion related to af’al al-‘ibad, the absolute power of Allah, the nature of Allah, the words of Allah and the fact that the faith was deemed sufficient to represent the thoughts of Imam Shafi'i in matters related to the Islamic faith. A text study adopted from the books of turath contains his thought of the Islamic faith has become the main reference in order to get the thought of the Islamic belief discussed thoroughly and able to be a reference for a relevant discussion. Although, this article is never referring to a writing or Theology debate, besides, the terms used by the group of the Theology scholars in discussing about Imam al-Shafi’i’s thought of the Islamic belief due to the concerning of any combination (syncretism) happens between the thought of Imam al-Shafi’i with other thoughts. The result of the analysis clearly shows that the Imam al-Shafi'i’s point of view about faith clearly has its own characteristics and at the slightly different path from the Muktazilah’s faith point of view despite of there are some still the same but are pretty close with the Asyariah understanding and in fact there is still a different.